2018
DOI: 10.1177/0890334418773302
|View full text |Cite
|
Sign up to set email alerts
|

Social Support for Breastfeeding in the Era of mHealth: A Content Analysis

Abstract: Although freely available mobile applications and text-messaging programs exist, with potential for wide reach, the majority provide only informational support. These programs would benefit from additional study of their usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
4
22
0
2
Order By: Relevance
“…Participants also suggested that during health visits, physicians, nurses, or health promoters can use the mHealth tool to explain standardized health information and provide access to the mHealth tool for caregivers to use beyond the encounter. Similar findings have been reflected in previous research in the development and assessment of mHealth interventions in other countries, including India and Germany [ 12 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Participants also suggested that during health visits, physicians, nurses, or health promoters can use the mHealth tool to explain standardized health information and provide access to the mHealth tool for caregivers to use beyond the encounter. Similar findings have been reflected in previous research in the development and assessment of mHealth interventions in other countries, including India and Germany [ 12 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 90%
“…To address this significant child health issue, breastfeeding promotion interventions emphasizing early initiation and EBF until 6 months of age are critical. These must be effectively designed and utilized in settings such as the Dominican Republic and other LMICs where challenges persist in providing high-quality, easily accessible EBF care and support [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the work of Schindler-Ruwisch et al, we found that for-profit companies and large businesses are more likely to create free breastfeeding apps [38]. Schindler-Ruwisch et al completed a content analysis of 53 breastfeeding apps in which they established that the majority of breastfeeding apps were free and developed by for-profit organizations [38]. Their review was limited in scope because the apps were not downloaded and explored; thus, features and educational content were not comprehensively assessed.…”
Section: Discussionsupporting
confidence: 87%
“…These results corroborate the study by Guijarro et al, 15 which used a similar strategy and obtained a higher percentage of breastfeeding (36% vs. 18.5%) after 6 months of age, level of evidence N4. A content analysis developed by Schindler-Ruwisch et al 37 identified that, just like mobile applications, text messaging is a potentially far-reaching resource in providing information about breastfeeding. 38 Austen et al 39 present the use of video with musical parody as an additional resource to sensitize young adults about the importance of breastfeeding.…”
Section: Alam Et Al (2017)mentioning
confidence: 99%